IMPROVING THE LITERACY OF VISUALLY IMPAIRED STUDENTS IN UNDERSTANDING NAHWU AND SHARAF THROUGH THE USE OF THE JURUMIYAH BRAILLE MODULE AT GARUNGGUNG ISLAMIC BOARDING SCHOOL, KARAWANG - Permana, Hinggil; Masruroh, Siti; Rochimah, Nur; Adiputrajaya, Prima; Purwanto, Wildan Barizi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Garunggung Islamic Boarding School in Karawang faces significant challenges in providing access to the study of Nahwu and Sharaf for visually impaired students due to the absence of classical Islamic texts in Braille format. Situation analysis revealed limited learning materials, lack of teacher training, and low student independence as the main problems. A community service program introducing the Jurumiyah Braille Module was implemented by producing the Jurumiyah text in Braille, training teachers in inclusive teaching methods, and providing supporting technology such as Braille printers. The results show improved literacy in Nahwu and Sharaf, increased student independence, and enhanced teacher capacity in Braille-based instruction. This program demonstrates that combining technological innovation, teacher training, and mentoring can create inclusive and equitable religious education for visually impaired students in Islamic boarding schools.